2011
DOI: 10.1099/vir.0.030494-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of cyclin-dependent kinase 9 to nuclear compartments during cytomegalovirus late replication: importance of an interaction between viral pUL69 and cyclin T1

Abstract: Cyclin-dependent protein kinases (CDKs) are important regulators of cellular processes and are functionally integrated into the replication of human cytomegalovirus (HCMV). Recently, a regulatory impact of CDK activity on the viral mRNA export factor pUL69 was shown. Here, specific aspects of the mode of interaction between CDK9/cyclin T1 and pUL69 are described. Intracellular localization was studied in the presence of a novel selective CDK9 inhibitor, R22, which exerts anti-cytomegaloviral activity in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 63 publications
0
46
0
Order By: Relevance
“…Since CDK9/cyclin T1 complex was reported previously to be required for the replication of other viruses of Herpesviridae origin, we next verified the antiviral effect of FIT-039 on tion through phosphorylation of the CTD of RNA polymerase II and viral proteins, such as the ICP22 of HSV. The ICP22-CDK9 complex was reported previously to phosphorylate the CTD of RNA polymerase II and regulate the transcription of HSV (20,22). A previous study showed that CDK9 was localized to nuclear viral transcriptosomes at the immediate-early stage of the HCMV infection, which allowed the active transcription of HCMV IEGs (14).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Since CDK9/cyclin T1 complex was reported previously to be required for the replication of other viruses of Herpesviridae origin, we next verified the antiviral effect of FIT-039 on tion through phosphorylation of the CTD of RNA polymerase II and viral proteins, such as the ICP22 of HSV. The ICP22-CDK9 complex was reported previously to phosphorylate the CTD of RNA polymerase II and regulate the transcription of HSV (20,22). A previous study showed that CDK9 was localized to nuclear viral transcriptosomes at the immediate-early stage of the HCMV infection, which allowed the active transcription of HCMV IEGs (14).…”
Section: Discussionmentioning
confidence: 94%
“…CDK1 was shown to activate the expression of HSV-1 late genes (19), while CDK2 promoted the replication of adenovirus, papillomavirus, and herpes virus DNAs (7). CDK7 and CDK9 were shown to activate viral RNA transcription in HIV and HSV (7,14,15,(20)(21)(22)(23)(24). Feichtinger et al recently described the interaction between CDK9/cyclin T1 and viral mRNA export factor pUL69 in human cytomegalovirus (HCMV), which belongs to the β subgroup of Herpesviridae (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information on the localization of viral and cellular proteins required for viral RNA transcription. In infected cells, both phosphorylated (transcriptionally active) and unphosphorylated (transcriptionally inactive) forms of RNA polymerase II concentrate within nuclear structures thought to be replication compartments (Feichtinger et al, 2011). Within these structures, unphosphorylated and phosphorylated forms of RNA polymerase II localize with the viral protein UL69 (Feichtinger et al, 2011), which is known to be required for viral RNA processing and export to the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…In infected cells, both phosphorylated (transcriptionally active) and unphosphorylated (transcriptionally inactive) forms of RNA polymerase II concentrate within nuclear structures thought to be replication compartments (Feichtinger et al, 2011). Within these structures, unphosphorylated and phosphorylated forms of RNA polymerase II localize with the viral protein UL69 (Feichtinger et al, 2011), which is known to be required for viral RNA processing and export to the cytoplasm. The localization of RNA polymerase II in relation to UL44 has yet to be described; however, viral proteins involved in transcription and RNA metabolism, for example IE1, IE2 and UL84 (Bender et al, 2014;Silva et al, 2010), are found throughout the nucleus and co-localize with UL44 in viral replication compartments.…”
mentioning
confidence: 99%